Controlled release devices as adjuvants in nonsurgical periodontal therapy: A systematic review - Samuel Chillavert Dias Pascoal; Maria Clara Ayres Estellit; Karlos Eduardo Rodrigues Lima; Eduardo da Cunha Queiroz; Talita Arrais Daniel Mendes (Journal of Indian Society of Periodontology, 2023)
Controlled release devices (CRD) have been widely studied regarding their application in periodontal therapy. Therefore, the present study aims to evaluate the use and effectiveness of controlled-release devices in nonsurgical periodontal therapy through a systematic review. The research was carried out in six different databases, namely: Online Medical Literature Search and Analysis System (Medline-PubMed), Web of Science, Science Direct, Scopus, Scielo, and Google Scholar. The descriptors “Delayed-Action Preparation,” “Therapeutics,” and “Periodontitis,” were used with their EntryTerms and connected through the Boolean operators AND and OR. A total of 2847 studies were found, and after applying the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist flowchart, 34 were selected using the eligibility criteria. After that, the qualitative results were tabulated and the risk of bias in each of them was evaluated. It can be observed that the use of CRD presents itself as a successful alternative for adjuvant treatment to periodontal therapy, a fact due to its availability and local concentration in the crevicular fluid. However, further clinical research is still needed to develop devices that are effective, with an easy and quick application, as well as available at a good cost–benefit ratio.